Prevalence of Depression in Pregnant Women with Bariatric Surgery History and Associated Factors - da Rocha, Andréa Christina Nowak; da Cunha, Ana Cristina Barros; da Silva, Jaqueline Ferreira (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2022)
Objective To analyze the prevalence and factors associated with depressive symptoms among Brazilian pregnant women with history of bariatric surgery (BS).Methods This is a cohort study with 247 women who got pregnant after BS. Based on data collection via Google Form, the recruitment of participants occurred in Facebook groups for 13 months. All of them answered a form with Informed Consent, a general data protocol and the Brazilian version of the Depression, Anxiety and Stress Scale-21. Descriptive and inferential analysis were performed, and a binary logistic regression model was tested to predict the factors associated with depressive symptoms.Results The prevalence of depressive symptoms was 32.8%, noted as being higher in the first (40.6%) and third (34.3%) gestational trimesters. Significative associations were found between depression and marital status (p = 0.000), planned pregnancy (p = 0.001), desired pregnancy (p = 0.004) and psychiatric history (p = 0.000). Women who were not married (odds ratio, OR = 3,38; p = 0.002) and had a psychiatric history (OR = 2.70; p = 0.102) had higher chances of showing depression symptoms; while planned and desired pregnancy showed as protective factors to the symptoms of depression.Conclusion These findings highlight the importance of psychological assistance for pregnant women with history of BS, to prevent development of mental disorders and their outcomes for maternal-child health.
Keywords: bariatric surgery; pregnancy; mental health; depression; perinatal care